2000
DOI: 10.1017/s1355617700611062
|View full text |Cite
|
Sign up to set email alerts
|

Elucidating the contributions of processing speed, executive ability, and frontal lobe volume to normal age-related differences in fluid intelligence

Abstract: One theory of normal cognitive aging asserts that decreases in simple processing speed mediate the age-related decline of fluid intelligence. Another possibility is that age-related atrophic changes in frontal brain structures undermine the functioning of executive abilities, thereby producing the same decline. In this study, we used principal components analysis to derive a measure of fluid-spatial intelligence in 197 normal adults between 20 and 92 years of age. Measures of perceptual comparison speed, worki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
94
0
5

Year Published

2005
2005
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 173 publications
(110 citation statements)
references
References 41 publications
11
94
0
5
Order By: Relevance
“…However, it would appear that the influence was limited to psychomotor speed, as only TMT-A performance was significantly predicted by gender. In addition, our results indicated that TMT-B was influenced by a small but significant effect of education, which is consistent with the more general effect of this variable on executive function (Daigneault & Braun, 1993;Fisk & Warr, 1996;Keys & White, 2000;Schretlen et al, 2000;Van der Linden, Beerten, & Pesenti, 1998;West, 2001). The influence of education was of particular interest due to the relative absence of education-adjusted normative data in the literature.…”
Section: Discussionsupporting
confidence: 87%
“…However, it would appear that the influence was limited to psychomotor speed, as only TMT-A performance was significantly predicted by gender. In addition, our results indicated that TMT-B was influenced by a small but significant effect of education, which is consistent with the more general effect of this variable on executive function (Daigneault & Braun, 1993;Fisk & Warr, 1996;Keys & White, 2000;Schretlen et al, 2000;Van der Linden, Beerten, & Pesenti, 1998;West, 2001). The influence of education was of particular interest due to the relative absence of education-adjusted normative data in the literature.…”
Section: Discussionsupporting
confidence: 87%
“…Specifically, greater anterior cingulate volume was associated with less time needed to complete the Stroop Inhibition Task, whereas larger orbitofrontal volumes were associated with poorer verbal fluency. Other studies show that, in older adults, smaller PFC gray-matter volume [Gunning-Dixon and Raz, 2003] and smaller right frontal-lobe volume [Hanninen et al, 1997] were related to a higher number of perseverative errors in the WCST, and that larger frontal-lobe volume was positively linked to the number of completed WCST categories [Schretlen et al, 2000].…”
Section: Introductionmentioning
confidence: 94%
“…The CCF (scale 3) consists of 50 items and assesses inductive reasoning through the ability to perceive relationships in shapes and figures. Age-adjusted IQ scores were used because fluid intelligence has been shown to decline with age (Schretlen et al 2000). The two groups did not differ in mean IQ (young adult group: M=120.2, SD=19.7; senior group: M= 123.8, SD=21.1) [t(82)=−0.804, P<0.424].…”
Section: Demographic and Cognitive Testsmentioning
confidence: 99%